Sistem Informasi Inventory Barang Dengan Metode FIFO Berbasis Website di Divisi Product Supply Robonesia.ID - Fresa Dwi Juniar Sofalina; Nadia Handayani (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Inventory Information Systems Have A Major Influence For Several Companies To Manage And Report Warehouse Data. Therefore, A Web-Based Product Supply Division Inventory Information System Was Created At Rumah Robot Indonesia (Robonesia.Id) To Make It Easier For Product Supply Employees In Terms Of Managing The Entry And Exit Of Goods And Stock Availability. This Website Was Created As A Solution To Various Problems That Arise In The Product Supply Warehouse Management Activities Of Rumah Robot Indonesia (Robonesia.Id). This Website Was Created Using The Php, Css, And Javascript And The Database Using Mysql. The Research Method Used Is The Fifo (First In First Out) Method. Tools In Analysis And Design Include Usecase Diagrams, Class Analisys Diagrams, Sequence Diagrams And Data Dictionaries As Well As Designing Databases Of System Test Results Using Black Box. With The Implementation Of Managing The Entry And Exit Of Goods And The Availability Of Goods In The Warehouse, It Is Hoped That It Can Help Employees Manage Product Supply Inventory, Making It Easier For Work To Achieve The Desired Work Results And Be Able To Find Information Quickly That Does Not Need To Take A Lot Of Time.